Trans-cinnamaldehyde protected PC12 cells against oxygen and glucose deprivation/reperfusion (OGD/R)-induced injury via anti-apoptosis and anti-oxidative stress - Xue Qi; Ru Zhou; Yue Liu; Jing Wang; Wan-Nian Zhang; Huan-Ran Tan; Yang Niu; Tao Sun; Yu-Xiang Li; Jian-Qiang Yu (Molecular and Cellular Biochemistry, 2016)

New process for copper migration by bioelectricity generation in soil microbial fuel cells - Hui Wang; Hailiang Song; Ran Yu; Xian Cao; Zhou Fang; Xianning Li (Environmental Science and Pollution Research, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

Procalcitonin levels in patients with positive blood culture, positive body fluid culture, sepsis, and severe sepsis: a cross-sectional study - Ying Yu; Xia-Xi Li; Ling-Xiao Jiang; Meng Du; Zhan-Guo Liu; Zhong-Ran Cen; Hua Wang; Zhen-Hui Guo; Ping Chang (Infectious Diseases, 2016)